Normative need in relation to perceived oral health among institutionalized adults of South India: A cross-sectional study - S Hari Krishnam Raju; Fareed Nusrath; K M Sudhir; R.V.S Krishna Kumar; K Vandana (Wolters Kluwer Medknow Publications, 2016)
Introduction: The number of adult individuals living alone is rising worldwide, especially in India, and their oral health-related quality of life is an increasing public health concern. Aim: The aim of the study is to assess the impact of periodontal status and dental caries experience on perceived oral health among institutionalized adults. Materials and Methods: A cross-sectional study was conducted among institutionalized adults in Nellore district of Andhra Pradesh. Self-perceived oral health was assessed using Geriatric Oral Health Assessment Index (GOHAI). Clinical examination was done for recording the periodontal status and dental caries according to the World Health Organization criteria (1997). Results: A total of 328 subjects were included with a mean age of 69.7 years. The mean GOHAI score of dentate participants was 48.24 (standard deviation [SD] 5.93). The overall prevalence of periodontal disease in the present study was 89.09% and mean caries experience was 10.85 (SD 9.36). There was a negative correlation between GOHAI scores and periodontal status and dental caries experience among the study participants. Conclusion: Low oral health, self-perception is directly correlated with a worse oral health; hence, perceived oral health can be a surrogate measure for clinical oral examination.